Proceedings of the Web Conference 2020 2020
DOI: 10.1145/3366423.3380212
|View full text |Cite
|
Sign up to set email alerts
|

Finding large balanced subgraphs in signed networks

Abstract: Signed networks are graphs whose edges are labelled with either a positive or a negative sign, and can be used to capture nuances in interactions that are missed by their unsigned counterparts. The concept of balance in signed graph theory determines whether a network can be partitioned into two perfectly opposing subsets, and is therefore useful for modelling phenomena such as the existence of polarized communities in social networks. While determining whether a graph is balanced is easy, finding a large bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In the context of polarized groups, one would expect that nodes within the same group are positively connected, while nodes from different groups are negatively connected. Recent research has suggested that identifying balanced subgraphs can serve as a useful proxy for discovering polarized communities within signed networks (Bonchi et al 2019;Ordozgoiti, Matakos, and Gionis 2020;Tzeng, Ordozgoiti, and Gionis 2020;Xiao, Ordozgoiti, and Gionis 2020). However, a common drawback found in these studies is their reliance on a poorly-L1→L0 QTs…”
Section: Related Workmentioning
confidence: 99%
“…In the context of polarized groups, one would expect that nodes within the same group are positively connected, while nodes from different groups are negatively connected. Recent research has suggested that identifying balanced subgraphs can serve as a useful proxy for discovering polarized communities within signed networks (Bonchi et al 2019;Ordozgoiti, Matakos, and Gionis 2020;Tzeng, Ordozgoiti, and Gionis 2020;Xiao, Ordozgoiti, and Gionis 2020). However, a common drawback found in these studies is their reliance on a poorly-L1→L0 QTs…”
Section: Related Workmentioning
confidence: 99%
“…In [23], Tsourakakis et al considered dense graph detection problems with negative weights. Ordozgoiti et al [24] proposed a more efficient and scalable approach to this problem.…”
Section: Related Workmentioning
confidence: 99%